Analisa Laju Korosi dan Kekerasan Pada Stainless Steel 316 L Dalam Larutan 10 % NaCl Dengan Variasi Waktu Perendaman - Arga Jeremia Sinaga; Charles Manurung (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2020)
Corrosion is an electrochemical reaction between metals and the environment that causes corrosion and decreases the quality of metals. Steel is a metal material that is widely applied in the industrial world. Stainless steel is stainless steel that is resistant to corrosion because it has an alloying element of at least 18% chrome and 8% nickel. To find out the superiority of stainless steel as a construction material, research on local corrosion of stainless steel needs to be done. For this reason, research on corrosion is carried out by using a 10% NaCl salt solution by varying the immersion time of stainless steel in corrosive media. From the research results it is known that the type of corrosion that occurs in specimens is the type of uniform corrosion. Likewise with the value of violence will decrease if the stainless steel is soaked longer.